Evaluation of CML TKI Induced Cardiovascular Toxicity and Development of Potential Rescue Strategies in a Zebrafish Model - Cheng, Shan; Jin, Pan; Li, Heying; Pei, Duanqing; Shu, Xiaodong (Frontiers in Pharmacology, 2021)
Tyrosine kinase inhibitors (TKIs) to BCR-ABL1 have been successfully used to treat chronic myeloid leukemia (CML), however, multiple TKI-associated adverse events have been reported and become an emerging problem in patients. The mechanisms of TKI-induced toxicity are not fully understood and it remains challenging to predict potential cardiovascular toxicity of a compound. In this study, we established a zebrafish model to evaluate potential in vivo cardiovascular toxicity of TKIs. We treated the endothelium labeled Tg(kdrl:EGFP) transgenic zebrafish embryos with TKIs then performed confocal imaging to evaluate their vascular structure and function. We found that among FDA approved CML TKIs, ponatinib (the only approved TKI that is efficacious to T315I mutation) is the most toxic one. We then evaluated safety profiles of several clinical stage TKIs that can target T315I and found that HQP1351 treatment leads to vasculopathies similar to those induced by ponatinib while the allosteric ABL inhibitor asciminib does not induce noticeable cardiovascular defects, indicating it could be a promising therapeutic reagent for patients with T315I mutation. We then performed proof-of-principle study to rescue those TKI-induced cardiovascular toxicities and found that, among commonly used anti-hypertensive drugs, angiotensin receptor blockers such as azilsartan and valsartan are able to reduce ponatinib or HQP1351 induced cardiovascular toxicities. Together, this study establishes a zebrafish model that can be useful to evaluate cardiovascular toxicity of TKIs as well as to develop strategies to minimize TKI-induced adverse events.